#TITLE_ALTERNATIVE# - (NIM 230 99 049), Widayat
Abstract : Efficient production of fuel ethanol could fruitfully contribute to the solution of the ever-growing problem of sustainable provision of energy to mankind. Ethanol can be produced by fermentation of a renewable raw material, i.e. carbohydrate. The objective of this research is to select and create an energy-efficient process configuration and Heat Exchanger Network (HEN) for separating and purifying ethanol from fermentation broth. In this research, the Danish Distilleries process was chosen as the fermentation stage to produce the ethanol-containing broth. Three basic process configurations were selected for the study, each consisted of a combination of Danish Distilleries process with a separation system yielding 95% (v/v) ethanol. The three separation systems are Barbel process, Othmer process and a separation process that operates under vacuum (see. Figs a, b and c). The production capacity of the plant is assumed to be 4 x 10 liter of ethanol 95% (v/v) per year. The equations of Wilson, Margules and NRTL (Non Random Two Liquid) were used to predict the ethanol -ater phase equilibrium and compared to available experimental data. The Wilson equation yield a better prediction compared the other equations and, therefore, was then incorporated into the computer program calculating the mass and energy balances of three processes. The results of the research show that the most energy efficient of three processes evaluated is process 2, followed by process 1 and process 3; the consumption of 3-atm steam of each process is respectively, 3,23; 4,11; 4,79 kg/liter ethanol. Further evaluation show that somewhat more saving in energy is possible by allowing AT.; = 10 C in heat exchangers : 0,4853 MW in process configuration 1. The saving in energy of process configuration 2 is 0,5084 MW when the reboiler (HE-3) in acetaldehyde stripper column was included in the HEN analysis. The saving in process configuration 1 increased to 0,5056 MW when the reboiler (H-3) in acetaldehyde stripper column was included in the HEN analysis. The improved flow diagrams of these two processes are presented in Figure d, e and f. Process configurations 4 and 5 (Figs. d and e) differ from process configuration I (Fig. a) in the media used to heat the (ethanol) stripper column feed and the acetaldehyde stripper reboiler. The stripper column feed is heated by the top product of the acetaldehyde stripper column in process configuration 1, and by stillage in process configuration 5 and by stillage and the bottom product of the rectifying column in process configuration 4. The acetaldehyde stripper reboiler is heated by steam (or utilities) dan fresh (hot) stillage in process configuration 4, and by steam in process configuration 1 and 5. Process configuration 6 (Fig. f) differs from process configuration 2 (Fig. b) in the medium used to heat the (ethanol) stripper column feed : the top product of the acetaldehyde stripper column in process configuration 2 and stillage in process configuration 6.